Giuseppe Chiovenda - Pérez Ragone, Álvaro; Salgado, José María (Pontificia Universidad Católica del Perú, 2017)
Conmemorando los ochenta años de la muerte de Giuseppe Chiovenda, el artículo analiza su aporte en la formación de la escuela procesal italiana, la recepción de sus ideas en Latinoamérica, su visión sobre la jurisdicción y la acción así como su pensamiento sobre el proceso oral.

Commemorating the eighty years of the death of Giuseppe Chiovenda, the paper analyzes his contribution in the formation of the Italian procedural school, the reception of his ideas in Latin America, his vision of the juris-diction and the action as well as his thought on the oral process.
Giuseppe Chiovenda
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01